Shifts in the age distribution and from acute to chronic coronary heart disease hospitalizations. (January 2016) - Koopman, Carla; Bots, Michiel L; van Dis, Ineke; Vaartjes, Ilonca
Background: Shifts in the burden of coronary heart disease (CHD) from an acute to chronic illness have important public health consequences. Objective: To assess age-sex-specific time trends in rates and characteristics of acute and chronic forms of CHD hospital admissions in the Netherlands. Methods: Using nationwide Dutch registers, we assessed time trends between 1998 and 2007 in hospitalization rates of 188, 266 acute myocardial infarction (AMI, ICD-9 410), 294, 374 unstable angina (ICD-9 411, 413) and 205, 649 chronic forms of CHD (ICD-9 412, 414) admissions. Results: Between 1998 and 2007, the age-standardized CHD hospitalization rate declined from 688 to 545 per 100, 000 in men and from 281 to 229 per 100, 000 in women. Overall, hospitalization rates decreased at younger age (<75 years) but increased in very old age (≥85 years). The annual percentage change in hospitalization rates was larger for AMI (men:-5.1%, women:-4.4%) than for unstable angina patients (men:-2.0%, women:-2.0%). For chronic CHD, the average annual percentage change was +0.7% in men and +2.1% in women. The proportion of chronic CHD in the total of CHD admissions increased between 1998 and 2007 from 29% to 36% in men and from 23% to 30% in women. The proportion of AMI decreased from 30% to 24% in men and from 27% to 22% in women. Conclusions: An increasing proportion of Dutch CHD hospital admissions was for chronic forms of CHD. The age at hospitalization was pushed towards older age: premature CHD admission declined over time and admission rates at very old age increased.